The reliability of virtual non-contrast reconstructions of photon-counting detector CT scans in assessing abdominal organs - Dudás, Ibolyka; Schultz, Leona; Benke, Márton; Szücs, Ákos; Kaposi, Pál Novák; Szijártó, Attila; Maurovich-Horvat, Pál; Budai, Bettina Katalin (BMC medical imaging, 2024)
Spectral imaging of photon-counting detector CT (PCD-CT) scanners allows for generating virtual non-contrast (VNC) reconstruction. By analyzing 12 abdominal organs, we aimed to test the reliability of VNC reconstructions in preserving HU values compared to real unenhanced CT images.